Palliative approach in acute neurological events: a five-year study - Monteiro,Nuno Ferreira (2018)
SUMMARY INTRODUCTION Acute neurological illness often results in severe disability. Five-year life expectancy is around 40%; half the survivors become completely dependent on outside help. OBJECTIVE Evaluate the symptoms of patients admitted to a Hospital ward with a diagnosis of stroke, subarachnoid hemorrhage or subdural hematoma, and analyze the role of an In-Hospital Palliative Care Support Team. MATERIAL AND METHODS Retrospective, observational study with a sample consisting of all patients admitted with acute neurological illness and with a guidance request made to the In-Hospital Palliative Care Support Team of a tertiary Hospital, over 5 years (2012-2016). RESULTS A total of 66 patients were evaluated, with an age median of 83 years old. Amongst them, there were 41 ischaemic strokes, 12 intracranial bleedings, 12 subdural hematomas, and 5 subarachnoid hemorrhages. The median of delay between admission and guidance request was 14 days. On the first evaluation by the team, the GCS score median was 6/15 and the Palliative Performance Scale (PPS) median 10%. Dysphagia (96.8%) and bronchorrhea (48.4%) were the most prevalent symptoms. A total of 56 patients had a feeding tube (84.8%), 33 had vital sign monitoring (50.0%), 24 were hypocoagulated (36.3%), 25 lacked opioid or anti-muscarinic therapy for symptom control (37,9%); 6 patients retained orotracheal intubation, which was removed. In-hospital mortality was 72.7% (n=48). DISCUSSION AND CONCLUSION Patients were severely debilitated, in many cases futile interventions persisted, yet several were under-medicated for symptom control. The delay between admission and collaboration request was high. Due to the high morbidity associated with acute neurological illness, palliative care should always be timely provided.